EXPLORING THE NEEDS AND LIVED EXPERIENCES OF FAMILY MEMBERS OF CRITICALLY ILL PATIENTS IN THE INTENSIVE CARE UNIT:A PHENOMENOLOGICAL STUDY - Budi santoso; Rachmawaty M. Noer; nauza agis irdiana; Yulianti Wulandari (Poltekkes Kemenkes Banten, 2026)
In addition to intensive medical care, the condition of critically ill patients also significantly impacts the physical, psychological, social, and spiritual well-being of accompanying family members. Limited access to information, strict visitation rules, and the high-pressure ICU environment often lead to anxiety, stress, and fatigue among family members.This phenomenon highlights the need for a deeper understanding of the needs and experiences of families as caregivers. This study aims to explore the needs and experiences of families of critically ill patients being treated in the ICU of Hospital X in Batam. This study was conducted using a qualitative approach. The research design applied was phenomenology. Data collection was carried out through in-depth interviews, designed in a semi-structured format to allow flexibility in responses. Data were obtained from five participants who were included in this study, selected through the convenience sampling technique. The data analysis process was carried out using thematic analysis. This study identified five main themes. First, Family Sacrifice and Responsibility. Second, The Physical and Emotional Burden of ICU Patient Families. Third, The Meaning of Prayer and Hope in Facing Critical Care. Fourth, The Essence of Togetherness in Patient Care. Fifth, Family Experiences with Hospital Services and Facilities. The study concludes that caregivers experience substantial physical and emotional burdens, yet continue to show deep concern and responsibility. Spiritual support, togetherness, and hospital services significantly shape their overall experience during the care process. Recommendations for Hospitals: Hospitals should provide emotional and educational support for families. Effective communication by healthcare professionals and flexible visitation policies can enhance families' comfort and trust as they accompany and support their loved ones. Keywords: Intensive Care Unit; family care giver; human needs; phenomenology; holistic care. In addition to intensive medical care, the condition of critically ill patients also significantly impacts the physical, psychological, social, and spiritual well-being of accompanying family members. Limited access to information, strict visitation rules, and the high-pressure ICU environment often lead to anxiety, stress, and fatigue among family members.This phenomenon highlights the need for a deeper understanding of the needs and experiences of families as caregivers. This study aims to explore the needs and experiences of families of critically ill patients being treated in the ICU of Hospital X in Batam. This study was conducted using a qualitative approach. The research design applied was phenomenology. Data collection was carried out through in-depth interviews, designed in a semi-structured format to allow flexibility in responses. Data were obtained from five participants who were included in this study, selected through the convenience sampling technique. The data analysis process was carried out using thematic analysis. This study identified five main themes. First, Family Sacrifice and Responsibility. Second, The Physical and Emotional Burden of ICU Patient Families. Third, The Meaning of Prayer and Hope in Facing Critical Care. Fourth, The Essence of Togetherness in Patient Care. Fifth, Family Experiences with Hospital Services and Facilities. The study concludes that caregivers experience substantial physical and emotional burdens, yet continue to show deep concern and responsibility. Spiritual support, togetherness, and hospital services significantly shape their overall experience during the care process. Recommendations for Hospitals: Hospitals should provide emotional and educational support for families. Effective communication by healthcare professionals and flexible visitation policies can enhance families' comfort and trust as they accompany and support their loved ones. Keywords: Intensive Care Unit; family care giver; human needs; phenomenology; holistic care. In addition to intensive medical care, the condition of critically ill patients also significantly impacts the physical, psychological, social, and spiritual well-being of accompanying family members. Limited access to information, strict visitation rules, and the high-pressure ICU environment often lead to anxiety, stress, and fatigue among family members.This phenomenon highlights the need for a deeper understanding of the needs and experiences of families as caregivers. This study aims to explore the needs and experiences of families of critically ill patients being treated in the ICU of Hospital X in Batam. This study was conducted using a qualitative approach. The research design applied was phenomenology. Data collection was carried out through in-depth interviews, designed in a semi-structured format to allow flexibility in responses. Data were obtained from five participants who were included in this study, selected through the convenience sampling technique. The data analysis process was carried out using thematic analysis. This study identified five main themes. First, Family Sacrifice and Responsibility. Second, The Physical and Emotional Burden of ICU Patient Families. Third, The Meaning of Prayer and Hope in Facing Critical Care. Fourth, The Essence of Togetherness in Patient Care. Fifth, Family Experiences with Hospital Services and Facilities. The study concludes that caregivers experience substantial physical and emotional burdens, yet continue to show deep concern and responsibility. Spiritual support, togetherness, and hospital services significantly shape their overall experience during the care process. Recommendations for Hospitals: Hospitals should provide emotional and educational support for families. Effective communication by healthcare professionals and flexible visitation policies can enhance families' comfort and trust as they accompany and support their loved ones. Keywords: Intensive Care Unit; family care giver; human needs; phenomenology; holistic care.